1993
DOI: 10.1161/01.atv.13.1.11
|View full text |Cite
|
Sign up to set email alerts
|

HDLs and alimentary lipemia. Studies in men with previous myocardial infarction at a young age.

Abstract: The plasma concentration, particle size, and chemical composition of high density lipoproteins (HDLs) are associated with the metabolism of triglyceride-rich lipoproteins (TGRLs). During alimentary lipemia there is active exchange of lipids and apolipoproteins between HDL and apolipoprotein B-containing lipoproteins. Whereas HDL has been assigned a protective role against the development of atherosclerosis, alimentary lipemia has been proposed to represent a potentially atherogenic state. We examined plasma HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…Several studies support the concept that an exaggerated alimentary lipaemia predisposes to coronary artery disease (CAD) [98,[131][132][133][134][135][136][137][138][139][140]. Karpe et al [98] compared post-prandial lipoprotein metabolism in healthy subjects and patients with CAD, and demonstrated an impaired post-prandial lipoprotein metabolism in the patient group. Moreover, experimental and clinical studies have demonstrated that TRL remnants are atherogenic [133][134][135][136][137][138][139][140].…”
Section: Clinical Significance Of Increased Post-prandial Lipaemiamentioning
confidence: 99%
“…Several studies support the concept that an exaggerated alimentary lipaemia predisposes to coronary artery disease (CAD) [98,[131][132][133][134][135][136][137][138][139][140]. Karpe et al [98] compared post-prandial lipoprotein metabolism in healthy subjects and patients with CAD, and demonstrated an impaired post-prandial lipoprotein metabolism in the patient group. Moreover, experimental and clinical studies have demonstrated that TRL remnants are atherogenic [133][134][135][136][137][138][139][140].…”
Section: Clinical Significance Of Increased Post-prandial Lipaemiamentioning
confidence: 99%
“…Several reports testify that the transfer of cholesteryl esters from HDL to the TRL fraction is enhanced during alimentary lipaemia [65±69]. As a result HDL is depleted of cholesterol, whereas the HDL particle concentration measured as apo A-I containing lipoprotein particles with and without apo A-II is unaffected by oral fat intake [70]. Theoretically, the transfer of cholesterol from HDL into the TRL pool may be regulated on two levels, first by the concentration of CETP, and secondly by the abundance of acceptor lipoproteins, which increases in the postprandial state, partly as a result of the delayed rate of TRL clearance.…”
Section: Intravascular Metabolism Of Trlmentioning
confidence: 99%
“…[Diabetologia (1994) proteins of intestinal origin were higher in patients with NIDDM [2]. In 1979 Zilversmit [3] suggested that triglyceride-rich lipoproteins of intestinal origin, especially the cholesteryl ester-rich chylomicron remnants, could play a very important role in atherogenesis, and since then, several reports have been published supporting this hypothesis [4][5][6][7][8][9][10]. Thus, our observation that postprandial lipaemia was increased in NIDDM raised the possibility that abnormalities in the metabolism of intestinally-derived lipoproteins may contribute to the increased risk of CHD in these patients.…”
mentioning
confidence: 99%